2015
DOI: 10.1002/ejsp.2104
|View full text |Cite
|
Sign up to set email alerts
|

When collective memories of victimhood fade: Generational evolution of intergroup attitudes and political aspirations in Belgium

Abstract: Collective memory theories propose that groups' remembrances of their past depend upon their current social situation. In Belgium, a significant proportion of Dutch speakers share a collective memory of past victimisation by French speakers and fight for an ever-larger autonomy of their region. Yet, as the respective economic, political and social situations of the linguistic regions of Belgium recently evolved with a reversal of fortunes, the current experience of younger Dutch speakers does not fit the tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 30 publications
6
62
0
7
Order By: Relevance
“…From this perspective, identity comes to be communicated and understood through the lens of social representations of history. Indeed, Rimé et al (2015) found that differences in social representations of past relations between different generations in the two main Belgian linguistic groups predicted Dutch-and French-speaking participants' levels of identification with their linguistic community and with Belgium. It is thus logical to infer that social representations of colonialism will impact national identification, which, in line with Branscombe and Doosje's (2004) model, will in turn affect group-based emotions, such as guilt and shame.…”
Section: National Identification Support For Reparations and Assignmentioning
confidence: 98%
See 1 more Smart Citation
“…From this perspective, identity comes to be communicated and understood through the lens of social representations of history. Indeed, Rimé et al (2015) found that differences in social representations of past relations between different generations in the two main Belgian linguistic groups predicted Dutch-and French-speaking participants' levels of identification with their linguistic community and with Belgium. It is thus logical to infer that social representations of colonialism will impact national identification, which, in line with Branscombe and Doosje's (2004) model, will in turn affect group-based emotions, such as guilt and shame.…”
Section: National Identification Support For Reparations and Assignmentioning
confidence: 98%
“…Similarly, we contend that colonialism arouses different social representations among inhabitants of formerly colonised and colonising countries. This might be due, on the one hand, to antagonist roles and perspectives adopted in the past and, on the other hand, to the different needs these representations are aimed to fulfil in the present (Rimé, Bouchat, Klein, & Licata, 2015;Wohl, Matheson, Branscombe, & Anisman, 2013).…”
mentioning
confidence: 99%
“…Several studies (e.g., Licata & Klein, 2005;Rimé, Bouchat, Klein, & Licata, 2015;Tavani, Collange, Rateau, Rouquette, & Sanitioso, 2017) have analysed the connections between collective memory and social identity. In a recent review, Páez, Bobowik, De Guissmé, Liu, and Licata (2016) summarized the main functions of collective memory, which are: a) to define the group and its continuity -, that is, to delineate the categorization of who belongs to the group and who does not, thereby mobilizing and (re)defining social identities; b) to define norms and values of the group, dictating how its members should behave and react to different situations; c) to increase the sense of group cohesion, since it constitutes shared representations within the group; d) to help define the relative value of the group, as it compares its past with that of other groups, while trying to maintain a positive ingroup image; e) to legitimize past, present and future behaviour of the group; f) to mobilize the sense of belonging to the ingroup, contributing to the tendency of group members to engage in collective projects due to their shared belonging; and g) to influence the current psychological state of group members, since individuals may present different emotions (such as guilt, shame or pride) when reminded of past achievements or misdeeds of their ingroup (Páez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Rimé, Bouchat, Klein, & Licata, 2015) has already shown that group differences in the endorsement of separatism in Belgium differed across generations. The present findings confirm that the two groups’ political attitudes are amenable to change.…”
Section: Discussionmentioning
confidence: 92%